DESIGN OF TEACHING MATERIALS FOR WRITING SKILL BASED REACT LEARNING MODEL USING DIGITAL LEARNING MEDIA - Farel Olva Zuve; Refisa Ananda (Seminar Internasional Riksa Bahasa, 2021)
The development of technology and information is used as supporting learning facilities for the development of teaching materials. The development of teaching materials that is supported by developments in technology and information will produce teaching materials that are suitable and easily mastered by students who are nicknamed generation Z. Students who are in generation Z are close to technological developments and easy to master technology. Therefore, teaching materials are needed that can increase their interest in understanding a material. One of them is teaching materials developed using digital media. Currently, digital media has various forms. The teaching materials that will be made are based on a learning model based on the constructivism approach. The learning model chosen is a REACT-based learning model. The REACT-based learning model refers to the learning steps which include: relating, experiencing, applying, cooperating, and transferring. The five steps of this learning model will be applied in making teaching materials using digital media. It is hoped that this teaching material will be able to improve the interest and ability of students in writing. This type of research is development research. By using quantitative and qualitative research methods. Data collection techniques were carried out by conducting tests, questionnaires, and interviews. The object of this research study is about the development of teaching materials in writing skills.